A CLINICAL STUDY TO EVALUATE THE RASAYANA EFFECT OF ASTHISHRINKHALAGHRITA IN JARA - Kavitha C. K; Waheeda Banu (International Journal of Ayurveda and Pharma Research, 2020)
Modern medicine has made a great deal of progress in understanding the aging process and in controlling age-associated health issues. The problems of Aged were neglected by Ayurvedic science and recently there started new advancements in this branch of Ayurveda which is insufficient for the current needs. This had led to lack of active longevity with more disability and dependency. Thus, this study was taken up to evaluate the Rasayana (Anti- ageing) effect of Asthishrinkhalaghrita in Jara janya vyadhi (Diseases due to senility). Methods: In present study, 30 subjects were diagnosed with the Jara janya vyadhi, selected randomly and were given with 15 ml of Asthishrinkhalaghrita in the morning for 30 days. The data obtained were recorded, tabulated and statistically analyzed using appropriate statistical methods. Results: Study showed mild improvement in overall treatment. Though no statistically significant results were obtained, there was a good improvement for the patient in Climbing stairs, Sleep disturbance, Shwasa vridhi (Dyspnoea), Malabadhata (Constipation), Agni mandya (loss of appetite)and weight gain with p value<0.05 and Slatha sandhi (laxity of joints)and walking with p value > 0.05. Conclusion: Thus Rasayana chikitsa can improve the longevity, positive health; provide the resistance to fight against the diseases, keeping the excellence in the tissues including mental faculties.